Clinical Case 13—An unusual culprit: challenging diagnosis, easy solution. (21st October 2022) - Ribeiro Mané, Fernando Guilherme; Flores, Rui; Conde, Inês; Silva, Rodrigo; Pires, Carla Marques; Medeiros, Paulo; Oliveira, Cátia; Costa, João; Marques, Jorge
Abstract: Presentation: A 59-year-old woman, with multiple cardiovascular risk factors, a history of CABG (left internal mammary artery—obtuse marginal artery; right internal mammary artery—left anterior descending artery) and PAD; presented to the emergency department with prolonged thoracic pain (3 hours) associated with dyspnea. She was hypertense at admission, but the remaining physical exam was unremarkable. Initial electrocardiogram showed descendent segment ST depression in the lateral leads (DI, aVL and V4-V6). Blood test showed a rise in troponin I 0.6 → 8.3 ng/mL). Cardiac catheterization demonstrated patency of both bypasses. However, a calcified stenosis (70–80%) of the left subclavian artery proximal to the emergence of the left internal mammary artery was observed. Diagnosis: The findings suggested a possible coronary subclavian steal syndrome (CSSS). Management: The patient was reevaluated and was found to have a systolic blood pressure differential of 18mmHg between the two arms. Despite anti-anginal therapeutic optimization, episodes of angina upon minimal exertion continued. Consequently, she was submitted to percutaneous subclavian artery angioplasty with symptom resolution and was discharged under dual antiplatelet therapy and high-intensity statin. Learning points: CSSS complicates 0.2–6.8% of the patients who have undergone CABG with a left internal mammary graft. Peripheral artery disease is its strongest predictor and atherosclerosis is the main pathogenic mechanism. In patients with suspected CSSS, physical examination is paramount, often showing a systolic blood pressure differential. Subclavian artery angiography should be performed, whenever it is relevant, during the coronary angiography. First-line therapy includes percutaneous angioplasty and optimal medical therapy.